Analisis Kemampuan Pemahaman Konsep Matematika Mahasiswa Program Studi Ekonomi Syariah - Isnaini Isnaini; Fatrima Santri Syafri; Betti Dian Wahyuni (Yayasan Darussalam Bengkulu, 2025)
The purpose of this research is to determine how well students understand mathematical concepts and what factors affect student ability in the economics mathematics course in the Islamic economics study program. The method used in this study is descriptive qualitative. The subjects of this research are Islamic economics students from semester 2E. The subjects were selected through purposive sampling techniques. Qualitative data on students' mathematical concept understanding were obtained through observation, documentation, tests, and interviews. Before analyzing the data, the researcher conducted data source triangulation. The data analysis technique in this study involves three stages: reduction, presentation, and conclusion drawing from the data. The research results classify students' mathematical concept understanding test scores into three categories: high ability, moderate ability, and low ability. For students in the high ability category, they can master all indicators of conceptual understanding, namely Rephrasing concepts, Applying concepts algorithmically, Providing examples or counterexamples of concepts, Presenting concepts in various representations, and Relating various concepts to their everyday life. Students in the moderate ability category are able to master 3 indicators: Rephrasing concepts, Applying concepts algorithmically, Providing examples or counterexamples of concepts. Students in the low ability category can only master 2 indicators, which are Rephrasing concepts, and Providing examples or counterexamples of concepts. Additionally, there are internal and external factors that influence students' understanding of mathematical concepts. Internal factors include self-confidence, interest in learning, and motivation to learn, while external factors include educational background and teaching methods.